Ethnomathemtical Exploration of Palue Cultural Tribe and Its Integration Toward Learning Process at Elementary School in Nusa Tenggara Timur (Journal of Primary Education, 2018)
This study aims to explore the existing forms of ethnomatematics in the Palue society and to analyze its relation to mathematical concepts in elementary school. In this study, qualitative data were obtained through observation of the community's activity and arterfak used in the activity. The other data were also obtained through interviews with the Palue community. The data are analyzed theoretically using theories relating to the relationship of ethnomatematics with the concepts of mathematics in elementary school. The results show that the ethnomatematic forms that exist in the Palue society culture include forms of artifacts used in traditional ceremonies, dances, livelihoods, tenun ikat activities and traditional games. These social activities have a certain relationship to mathematical concepts in elementary schools, namely the concept of numeral operations, two deminsion concept (square, rectangle, triangle, circle, rhombus, and kite), geometry concept (tubes, shperis, and cones) as well as concepts of the measurement (measurement of the length, mass, and time). Based on this matter, it can be concluded that Palue society in Palue culture contained elements of ethnomatematics that can be integrated in the mathematics learning in elementary school.